Physical activity promotion in Saudi Arabia: A critical role for clinicians and the health care system - Zahra Alahmed; Felipe Lobelo (Springer, 2018)
This work aimed to summarize the benefits of physical activity and the importance of counseling by a physician to promote physical activity in a primary health care setting in Saudi Arabia. Despite established evidence that physical activity is effective for reducing the risk of non-communicable diseases, as well as the importance and cost-effectiveness of physical activity counseling in the primary care setting, few studies have been conducted regarding physical activity counseling in Saudi Arabia.